Poster: We Are Well: Well-being superpowers - portraits of well-being ... - Burke, Geraldine; Pettengell, Priscilla; Hanger, Chris (Monash University, 2023)
The poster, ‘We Are Well: Well-being superpowers- portraits of well-being’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. The poster showcases drawings of our well-being superpowers alongside our portraits. Poster text: We are creating well-being portraits together as we mentor each other. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Nikki Browne, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara and local community Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, ...